ONLINE COLLEGE ADMISSION MANAGEMENT SYSTEM - Karunya G.; Reihana Fathima S. (Galaxy International Interdisciplinary Research Journal, 2022)
The project entitled “Online College Admission Management System” is designed and developed using PHP as the front end and backend as MySQL. This online website is developed for colleges/universities to make the admission process much easier and also helps in maintaining the database in an efficient way.The main goal of the project is to reduce manual work, increase the processing speed and ensure the reliability of data. The system has two modules. They are ADMIN and USER. Admin can select/reject the students who have registered for admission and the user can log in to the website to apply for the desired course. The users can apply only if they are eligible for the criteria given by the college for each course. The selected candidate will get a notification from the admin. Thus the system helps in minimizing the human process and also maintaining manual records of all the candidates.